Modeling of photovoltaic array output current based on actual performance using artificial neural networks - Ameen A.M.; Pasupuleti J.; Khatib T. (American Institute of Physics Inc., 2023)
Errors; Neural networks; Photovoltaic cells; Regression analysis; Generalized regression; Generalized regression neural networks; Mean absolute percentage error; Mean bias errors; Photovoltaic arrays; Photovoltaic modules; Prediction accuracy; Root mean square errors; Mean square error